Lifelong learning theory and pre-service teachers' development of knowledge and dispositions to work with Australian Aboriginal students. Issue 1 (2nd January 2016) - Bennet, Maria; Moriarty, Beverley
Abstract: This article draws on previous research by the authors and others as well as lifelong learning theory to argue the case for providing pre-service teachers with deep and meaningful experiences over time that help them to build their personal capacity for developing knowledge and dispositions to work with Australian Aboriginal students, their families and communities. These experiences, provided in partnership with the Aboriginal community, demonstrate how opportunities for deepening cultural understanding could help pre-service teachers to become key stakeholders in the partnership and to embrace the joint responsibility for working towards improving educational outcomes for Aboriginal students. The Healthy Culture Healthy Country Programme was developed by Dr. Shayne Williams of the New South Wales Aboriginal Education Consultative Group (AECG) for practicing teachers and modified for pre-service teachers by its author. It was found from an exploration of the experiences of first year pre-service teachers during and following their participation in the modified programme that they showed evidence towards Delor's Four Pillars of Lifelong Learning: learning to know, learning to do, learning to live together and with others and learning to be. The pre-service teachers who participated in the research provided suggestions for how their experiences could be extended and deepened over the later years of their degree. This research has important implications with regard to how participation in ongoing opportunities to increase cultural competence could help pre-service teachers to develop their personal capacity to work towards the Australian Institute for Teaching and School Leadership's Professional Teaching Standards.